1977
DOI: 10.1002/ange.19770891118
|View full text |Cite
|
Sign up to set email alerts
|

Photochemische [2+2]‐Cycloaddition zwischen parallelen CC‐ und NN‐Doppelbindungen

Abstract: Eine [π25s + π2s]‐Photocyclisierung zwischen nicht aktivierten CC‐ und NN‐Doppelbindungen wurde jetzt erstmals beim starren Molekül (1) beobachtet, das dabei in eine neuartige Käfigverbindung übergeht. In anderen Fällen scheiterte dieser Ringschluß an der rascheren N2‐Abspaltung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…[42] In the dioxide 23, the olefinic protons (δ 14(15)-H ϭ 6.46) are deshielded relative to those of 17 (δ 14(15)-H ϭ 6.13); obviously the ONNO double bond exerts an anisotropic influence. In 28a(b) the rather tilted oxime C15ϭNO double bond is confirmed by the IR band at 1570 cm -1 and by the signal at δ ϭ 157.9 (157.1) in the 13 C NMR spectra. The oxadiazolidines 24 (25) and 37 are characterized i.a.…”
Section: Full Papermentioning
confidence: 52%
See 3 more Smart Citations
“…[42] In the dioxide 23, the olefinic protons (δ 14(15)-H ϭ 6.46) are deshielded relative to those of 17 (δ 14(15)-H ϭ 6.13); obviously the ONNO double bond exerts an anisotropic influence. In 28a(b) the rather tilted oxime C15ϭNO double bond is confirmed by the IR band at 1570 cm -1 and by the signal at δ ϭ 157.9 (157.1) in the 13 C NMR spectra. The oxadiazolidines 24 (25) and 37 are characterized i.a.…”
Section: Full Papermentioning
confidence: 52%
“…[15] ) amenable to competitive N 2 elimination. However, in an early paper by Hünig and Berning [13] it was demonstrated that even in a DBH-NϭN/CϭC system cycloaddition can win over N 2 elimination. [14] In the respective N-oxides, elimination of NO, N 2 O and N 2 O 2 is generally, if it occurs at all, only a very slow process.…”
Section: Choice Of Substrates -General Aspectsmentioning
confidence: 97%
See 2 more Smart Citations
“…0340-5087/85/0200-0187/$ 01.00/0 plexation to undergo C-N bond formation with alkynes. In the organic chemistry of the N=N group, reactions with unsaturated hydrocarbons are known to occur only if the diazene group is activated by electron withdrawing groups in the a,a'-position, like the Diels-Alder reaction with dienes [8], or if favoured by a special steric situation like the intramolecular [2+2] photocycloaddition with a C=C bond [9].…”
mentioning
confidence: 99%